Landslide Emergency Response Preparedness in Mining Areas: Early Warning System Implementation - Chadarisman, Ardhila; Herdianto, Tedi Cahya Nusantara (Universitas Airlangga, 2025)
Introduction: Coal mining operations present serious risks due to landslip risks, necessitating the use of efficient early warning systems and emergency preparation. This paper examines the use of an early warning system called LASER (Land Sliding Alert) in comparison to direct direction from the supervisor using conventional radio at the KPC Sangatta mining operation of PT. Pamapersada Nusantara. The study aims to evaluate how the system affects workers' response to approaching landslides as well as their degree of preparedness. Method: The researchers collected 12 data over 3 months from the emergency drill and continue with observations, interviews and document review. Substantive data including risk management screening, landsliding warning accuracy and response were assessed so response time from worker can be gathered. Result: The results displayed a better performance in the LASER early warning system than conventional land sliding alert, achieving 100% reactivity and increased pace of evacuation. The system uses Internet of Things (IoT) to ensure immediate notification for all buildings at the same time using sirens and radio equipment that leads to faster reaction. The LASER system is 96% effective at warning employees in the statistical research. Conclusion: The research demonstrates that the LASER-based early warning system is extremely efficient in monitoring dangerous slope conditions in mining areas. It effectively addresses the issue of response time and ensures that personnel are well-prepared to respond promptly and effectively. The study emphasises the significance of employing sophisticated monitoring systems and resilient emergency protocols to mitigate the hazards associated with landslides. The application of the landsliding alert can be implemented in other mining areas, especially in open pit mining activities and make contributions ultimately result in a workforce that is safer and mining operations that are more sustainable.